1994
DOI: 10.1103/physrevc.50.1024
|View full text |Cite
|
Sign up to set email alerts
|

Charged hadron distributions in central and peripheral Si+Acollisions at 14.6AGeV/c

Abstract: The AGS spectrometer experiment E-802 has measured transverse mass spectra for charged hadrons over a wide rapidity interval in Si+Au, Si+Cu, and Si+Al reactions at 14.6A G Ve/c. These results are compared for two difFerent trigger conditions: central collisions corresponding to 7% of the inelastic cross section selected on multiplicity of charged particles and peripheral collisions corresponding to roughly 50'Fo of the inelastic cross section selected on high kinetic energy at zero degrees. The invariant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 27 publications
4
67
0
Order By: Relevance
“…In most studies η f was (like R) set constant such that η t (r) was a function of r only. This cannot reproduce the observed rapidity dependence of p ⊥ and of the inverse slopes of the m ⊥ -spectra [65,66]. In [63,64] it was shown that an η-dependence of R, with R(η) shrinking in the backward and forward rapidity regions keeping the slope η f /R in (43) fixed, is sufficient to fully repair this deficiency.…”
Section: Collective Expansion and K-dependence Of The Correlatormentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies η f was (like R) set constant such that η t (r) was a function of r only. This cannot reproduce the observed rapidity dependence of p ⊥ and of the inverse slopes of the m ⊥ -spectra [65,66]. In [63,64] it was shown that an η-dependence of R, with R(η) shrinking in the backward and forward rapidity regions keeping the slope η f /R in (43) fixed, is sufficient to fully repair this deficiency.…”
Section: Collective Expansion and K-dependence Of The Correlatormentioning
confidence: 99%
“…It has been shown that the single-particle m ⊥ -distributions of pions and heavier hadrons reflect a transversely expanding source [65,72,120]. Such spectra are sensitive to a different combination of T and η f [70,72].…”
Section: Combining Single-and Two-particle Spectramentioning
confidence: 99%
“…3 we plot B 2 for both deuterons (open symbols) and antideuterons (solid symbols), for a variety of other systems and beam energies [3,5,[17][18][19][20][21][22][23][24][25][26], and this paper. The present result for the most central 10% of the cross section is plotted as the larger solid circle and the corrected value as a smaller solid circle.…”
Section: (Received 5 November 1999)mentioning
confidence: 99%
“…Measurements of deuteron coalescence in high energy heavy ion collisions have been reported previously both at AGS energies [20][21][22][23][24] from 10 to 14.6 A·GeV/c and at SPS energies [25][26][27][28][29] at 200 or 158 A·GeV/c. Of these, the AGS results of Si+A [20] and Au+Au [22] collisions as well as the SPS results of [25] are of special importance for the present study because they also deal with the systematics of deuteron production as function of rapidity, centrality, mass and transverse mass.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the AGS results of Si+A [20] and Au+Au [22] collisions as well as the SPS results of [25] are of special importance for the present study because they also deal with the systematics of deuteron production as function of rapidity, centrality, mass and transverse mass. The data reported in [26][27][28] are preliminary versions of part of the presently reported results.…”
Section: Introductionmentioning
confidence: 99%